Impact of the OATP1B1 c.521T>C single nucleotide polymorphism on the pharmacokinetics of exemestane in healthy post‐menopausal female volunteers. (29th July 2017) - Gregory, B. J.; Chen, S. M.; Murphy, M. A.; Atchley, D. H.; Kamdem, L. K.
Summary: What is known and objective: OATP1B1 mediates the transport of a diverse range of amphiphilic organic compounds that include bile acids, steroid conjugates and hormones. This retrospective pharmacogenetic study was conducted to assess the impact of the OATP1B1 c.521T>C single nucleotide polymorphism (SNP) on the pharmacokinetics of the steroidal aromatase inhibitor drug exemestane in healthy volunteers. Methods: Exemestane (25 mg) was administered orally to 14 healthy post‐menopausal women. All of the 14 subjects were sampled for pharmacokinetic (PK) analyses and retrospectively genotyped for OATP1B1 c.521T>C (rs 4149056). Results and discussion: Of the 14 subjects enrolled in the study, five were carriers of the minor C allele ( OATP1B1 c.521TC+CC) and the remaining nine were carriers of the OATP1B1 c.521TT genotype. PK was assessed over 8 hours post‐dosing. Our results showed statistically significant differences ( P= .04) in the plasma exemestane AUC0‐8 between the OATP1B1 genotype groups. Our data also showed statistically significant differences ( P= .04) in the plasma AUC0‐8 of 17‐hydroexemestane (the major biologically active metabolite) between the OATP1B1 genotype groups. What is new and conclusion: Our data suggest that the OAPTP1B1 c.521T>C SNP may influence exemestane pharmacokinetics in humans. Abstract : Significant interindividual variability has been observed in the clinical response to aromatase inhibitors. The aim of our study was to assess the impact of the OATP1B1 c. 521 T>C single nucleotide polymorphism on the pharmacokinetics of exemestane in healthy volunteers.